Effects of delayed cord clamping on infants after neonatal period: A systematic review and meta-analysis. (April 2019) - Zhao, Yang; Hou, Rui; Zhu, Xiu; Ren, Lihua; Lu, Hong
Abstract: Background: The majority of current evidences simply showed the short-term benefits of delayed cord clamping, mainly focusing on the first week after birth. Without follow-up data, we can hardly come to the conclusion that delayed cord clamping may do more harm than good. Objective: To evaluate the long-term effects of delayed cord clamping compared with early cord clamping on infants after neonatal period. Design: Systematic review and meta-analysis of randomized controlled trials (RCTs). Data sources: PubMed, EMBASE, and the Cochrane Library were systematically searched from inception date to June 22, 2018 for randomized clinical trials comparing early cord clamping with delayed cord clamping in infants beyond 1 month of age. Review methods: Two reviewers independently assessed trial eligibility and quality and extracted all infants' follow-up data after one month of age, which were divided into two groups for analysis, with follow-up periods of less than 6 months (<6 months) and beyond 6 months (≥6 months) respectively. Results: A total of twenty RCTs were identified and included in this study. All data of the twenty studies were pooled for final meta-analysis (3733 infants). Among preterm deliveries, delayed cord clamping slightly increased hematocrit (6–10 weeks) and serum ferritin (6–10 weeks). For term infants, delayed cord clamping reduced the incidence of anemia after six months of age (≥6 months), iron deficiency (< 6 months, ≥6 months) and iron deficiency anemia (4–12 months), while increased mean corpuscular volume before six months of age (< 6 months), hemoglobin after six months of age (≥6 months), serum iron (2–4 months), total body iron (4–6 months), serum ferritin (< 6 months, ≥6 months) and transferrin saturation (2–12 months). There were no significant differences between early versus late cord clamping groups for other variables. Conclusion: Delayed cord clamping modestly improved hematological and iron status of both preterm and term infants after neonatal period. This affords cogent evidence on the practice of delayed cord clamping for medical staff, especially for countries and regions suffering from relatively higher prevalence rate of iron deficiency during infancy and childhood.